Teaching for diversity and social justice. - Adams, Maurianne; Adams, Maurianne; Bell, Lee Anne, 1949-; Goodman, Diane; Shlasko, Davey (Routledge, Taylor & Francis Group, 2023)
"For over 30 years, Teaching for Diversity and Social Justice has been the definitive sourcebook of theoretical foundations, pedagogical and design frameworks, and curricular models for social justice teaching practice. Thoroughly revised and updated, this fourth edition continues in the tradition of its predecessors to cover the most relevant issues and controversies in social justice education (SJE) in a practical, hands-on format. Filled with ready-to-apply activities and discussion questions, this book provides teachers and facilitators with an accessible pedagogical approach to issues of oppression in classrooms. The revised edition also focuses on providing students and participants with the tools needed to apply their learning about these issues. This fourth edition includes new and revised material for each of the core chapters in the book complemented by fully developed online teaching designs, including over 150 downloadables, activities, and handouts on the book's companion website. A classic for educators across disciplines and contexts, Teaching for Diversity and Social Justice presents a thoughtful, well-constructed, and inclusive foundation for engaging people in the complex and often daunting problems of discrimination and inequality in American society"--